Live Streaming Commerce Di Indonesia: Peran Ulasan, Rekomendasi, Dan Komunitas Dalam Membangun Kepercayaan Konsumen - Setiawan, Margareth; Aprianingsih, Atik; Amalia, Rizkia (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2025)
The rapid adoption of live streaming commerce (LSC) has revolutionized social commerce by merging video streaming with online purchase, especially on platforms such as TikTok. Although LSC provides ease and accessibility, the lack of physical interaction presents trust issues for users. This study examines the impact of social commerce constructs, recommendations, reviews, and communities—on the development of consumer trust in LSC and explores how this trust affects consumer involvement. A survey methodology was utilized, focusing on TikTok users in Indonesia who engaged in live streaming shopping. The results indicate that social commerce constructs, especially communities, significantly enhance consumer trust in LSC. This trust subsequently drives customer engagement, seen in activities such as likes, comments, and extended viewing during live streams. This research's novelty resides in recognizing community relationships as a primary influence on trust and involvement in LSC. The practical implications are fostering active customer groups and promoting reviews to increase trust and involvement, hence enhancing purchase intentions.